PENGARUH MODEL PROBLEM BASSED LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS ULASAN/REVIU FILM/DRAMA SISWA KELAS XI SMA SEMEN PADANG - Andria Catri Thamsin, Yulia Busti, Erizal Gani, (Universitas Negeri Padang, 2017)
This study has three objectives as follows: (1) Describe the skill of writing the review / review movie / drama of class XI students of SMA Semen Padang before using the audiovisual media-assisted bassed learning problem model. (2) to describe the skills of writing a review / review movie / drama of class XI students of SMA Semen Padang before using the model of bassed learning problem audiovisual media aids. (3) to describe the effect of bassed learning model model of audiovisual media aid on writing / review / Drama class XI students of SMA Semen Padang. Next Model Problem Bassed Learning abbreviated as PBL. This research type is quantitative research with experiment method. The design of this study used a single subject group. Students class XI SMA Semen Padang registered in 2016-2017 which amounted to 128 people. The sample of this research is the students of class XI of SMA Semen Padang determined by using technique with certain consideration (purposive sampling). The variable of this research is the skill of writing the review / movie / drama review before and after using the audiovisual media assisted PBL model of class XI students of SMA Semen Padang.Â Kata kunci: Pengaruh, model problem bassed learning berbantuan media audiovisual, menulis teks ulasan/reviu film/dramaÂ